(3HGYK GdfahS Edi RjGQI GdbOS GdTQja GdeMQhSs - (3GdaRGQj , EHQGgje Hf YHO GdQMef Hf EHQGgje Hf SHGY Hf GdaQcGM, HQgGf GdOjf CHh ESMGb,J (B729 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG efJNH ef aVGFd HjJ GdebOS hbH EHQGgje GdNdjd Udi Gddg Ydjg hSde , ZGdHg ef cJGH GdeSJbUi GdMGaX HgGAGdOjf Hf YSGcQ s
(3BNQgG (B:s
(3CeG HYO aGefY ef cGf jDef HGddg hGdjhe GdBNQ ai bQi GdOGQjjf aEPG QLY CgdgG agi dge hCMb Hge hGdSdGe s
(3Vef eLehY s
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B45 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B43s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B130 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B161 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B59 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs